Modified graphite negative electrode material and preparation method and application thereof
By dispersing sulfonated graphene and aminated carbon nanotubes on the surface of graphite, combined with the treatment of asphalt and inorganic nanomaterials, a modified graphite anode material with a core-shell structure is formed, which solves the problems of rate performance, energy density and the first time in the existing technology. The problem of Coulomb efficiency is difficult to balance, and efficient charge transfer and high energy density are achieved.
Patent Information
- Application Number
- CN202411394978.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-24
AI Technical Summary
While improving the rate performance, existing graphite anode materials are difficult to take into account high energy density and high first-time Coulomb efficiency, especially in thick electrode architectures, the charge transfer path is prolonged, resulting in delay in the reaction kinetics.
By dispersing sulfide graphene and amino carbon nanotubes and covering the surface of graphite, combine the fusion of asphalt and inorganic nanomaterials, and carbonize treatment to form a modified graphite negative material with a nuclear shell structure.
Achieve a high -power performance, high energy density, and high -end Kuron efficiency, avoid the reaction dynamic delay caused by the extension of the charge transmission path, and improve the fast charging capacity and energy density of the battery.
Smart Images

Figure CN119361628A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a modified graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in 3C products and power storage. Currently, commercial lithium-ion batteries mainly use carbon negative electrode materials such as natural graphite, artificial graphite, soft carbon and hard carbon. Among them, natural graphite is widely used as an important negative electrode material due to its high specific capacity, good charge and discharge platform and low cost.
[0003] In recent years, with the continuous development of new energy vehicles, the demand for the power performance of lithium-ion batteries has continued to increase, and higher and higher requirements have been put forward for the energy density, safety performance and cycle life of batteries, especially the energy density of batteries. In the research and development of high energy density batteries, the energy density of the battery system can be increased by designing a thick electrode architecture, that is, without changing the battery chemical system, the content of negative electrode active materials per unit volume of the battery is increased to increase the energy density of the battery system. Based on this, improving the energy density of batteries through thick electrode architecture design has received widespread attention.
[0004] Graphite is soft and has low hardness. It deforms when subjected to vertical pressure during the rolling stage, which reduces the gaps between the stacked graphite particles on the surface of the negative electrode, slowing down the diffusion rate of Li+ on the surface of the graphite electrode. In particular, the reaction kinetics of thick electrodes are inevitably delayed due to the extension of the charge transfer path in thick electrodes. When lithium-ion batteries are at higher rates, slow charge transfer becomes a key factor limiting the fast charging capability and energy density of the battery cell.
[0005] In order to solve this problem, those skilled in the art can improve its rate performance by slightly expanding the natural graphite to expand the interlayer spacing or create pores. However, expanding the interlayer spacing or creating pores can only increase the diffusion channel of Li+ between graphite layers, and does not change the diffusion rate of Li+ inside the graphite electrode. Those skilled in the art also improve it by a double-layer slurry coating method, that is, coating the surface of the negative electrode sheet with a high-strength negative electrode material to increase the strength of the graphite on the negative electrode surface and prevent the gap between the stacked graphite particles on the surface of the negative electrode from decreasing during the rolling stage. However, this modification method greatly reduces the initial coulomb efficiency of the battery.
[0006] Therefore, how to obtain a graphite negative electrode for lithium-ion batteries that has both high rate performance, high first coulombic efficiency and high energy density has become a key research project. Summary of the invention
[0007] In order to improve the defect that the graphite negative electrode in the prior art cannot take into account high rate performance, high energy density and high first coulombic efficiency at the same time, the present invention provides a modified graphite negative electrode material and a preparation method and application thereof, wherein the modified graphite negative electrode material can take into account high rate performance, high energy density and high first coulombic efficiency at the same time.
[0008] The object of the present invention is achieved through the following technical solutions:
[0009] A method for preparing a modified graphite negative electrode material, the preparation method comprising the following steps:
[0010] (1) mixing sulfonated graphene with water, performing ultrasonic dispersion, then adding aminated carbon nanotubes, and continuing ultrasonic dispersion to obtain a sulfonated graphene / carbon nanotube dispersion solution;
[0011] (2) transferring the sulfonated graphene / carbon nanotube dispersion solution of step (1) into a constant temperature water bath, adding graphite, and obtaining a suspension;
[0012] (3) filtering, washing and drying the suspension obtained in step (2) to obtain sulfonated graphene / carbon nanotube-coated graphite;
[0013] (4) adding the sulfonated graphene / carbon nanotube-coated graphite of step (3) and asphalt into a mixer and kneading them to obtain modified graphite;
[0014] (5) adding the modified graphite and inorganic nanomaterials of step (4) into a fusion machine for fusion to obtain a fusion product;
[0015] (6) Carbonizing the fusion product of step (5) to obtain the modified graphite negative electrode material.
[0016] According to an embodiment of the present invention, in step (1), the mass of sulfonated graphene added per milliliter of water is (0.5-1.0) mg, for example, 0.5 mg, 0.6 mg, 0.7 mg, 0.8 mg, 0.9 mg or 1.0 mg.
[0017] According to an embodiment of the present invention, in step (1), the power and time of the ultrasound are not particularly limited, as long as the sulfonated graphene and the amino carbon nanotubes can be evenly dispersed. Exemplarily, the sulfonated graphene is mixed with water and ultrasonically dispersed for 1-10 hours, then the amino carbon nanotubes are added, and ultrasonic dispersion is continued for 2-6 hours to obtain a sulfonated graphene / carbon nanotube dispersion solution.
[0018] According to an embodiment of the present invention, in step (1), the sources of the sulfonated graphene and the amino carbon nanotubes are not particularly defined, and they may be prepared by methods known in the art, or purchased from commercial sources.
[0019] According to an embodiment of the present invention, in step (1), the mass ratio of the amino carbon nanotubes to the sulfonated graphene is (10-30):100, for example, 10:100, 15:100, 20:100, 25:100 or 30:100.
[0020] According to an embodiment of the present invention, in step (2), the temperature of the constant temperature water bath is 80-95°C, for example, 80°C, 85°C, 90°C or 95°C.
[0021] According to an embodiment of the present invention, in step (2), the graphite is added under stirring conditions, and the stirring time is 5-10 hours.
[0022] According to an embodiment of the present invention, in step (2), the graphite is selected from at least one of natural graphite and artificial graphite.
[0023] According to an embodiment of the present invention, in step (2), the median particle size of the graphite is 5-25 μm, for example, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm or 25 μm.
[0024] According to an embodiment of the present invention, in step (2), the mass ratio of the sulfonated graphene to graphite is (0.5-1):100, for example, 0.5:100, 0.6:100, 0.7:100, 0.8:100, 0.9:100 or 1:100.
[0025] According to an embodiment of the present invention, in step (3), the filtration is performed by methods known in the art, such as suction filtration, centrifugal filtration, etc.
[0026] According to an embodiment of the present invention, in step (3), the washing is performed using methods known in the art, such as washing with deionized water.
[0027] According to an embodiment of the present invention, in step (3), the drying temperature is 80-100°C.
[0028] According to an embodiment of the present invention, in step (4), the asphalt is selected from coal asphalt or petroleum asphalt.
[0029] According to an embodiment of the present invention, in step (4), the softening point of the asphalt is 120-180°C, for example, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C.
[0030] According to an embodiment of the present invention, in step (4), the asphalt is in powder form, and the particle size is preferably 1-3 μm, for example, 1 μm, 2 μm or 3 μm.
[0031] According to an embodiment of the present invention, in step (4), the mass ratio of the asphalt to the sulfonated graphene / carbon nanotube-coated graphite is (1-5):100, for example, 1:100, 2:100, 3:100, 4:100 or 5:100.
[0032] According to an embodiment of the present invention, in step (4), the kneading temperature is 80-100° C., the kneading speed is 50-500 r / min, and the kneading time is 1-300 min.
[0033] According to an embodiment of the present invention, in step (4), the kneading is performed under an air atmosphere.
[0034] According to an embodiment of the present invention, in step (4), the mixer is selected from at least one of a high-speed modified VC mixer, a cone mixer or a kneader.
[0035] According to an embodiment of the present invention, in step (5), the inorganic nanomaterial is selected from at least one of VN, Li3N, CoN, NiN, AlN, TiO2 and Al2O3.
[0036] According to an embodiment of the present invention, in step (5), the particle size of the inorganic nanomaterial is 10-30 nm, for example, 10 nm, 15 nm, 20 nm, 25 nm or 30 nm.
[0037] According to an embodiment of the present invention, in step (5), the rotation speed of the fusion is 50-500 r / min, and the fusion time is 30-100 min.
[0038] According to an embodiment of the present invention, in step (5), the fusion is performed under an air atmosphere.
[0039] According to an embodiment of the present invention, in step (5), during the fusion process, the modified graphite and the inorganic nanomaterials are continuously subjected to friction, extrusion and shear forces in a high-speed rotating cylinder. Under the action of friction, extrusion and shear forces, the asphalt on the surface of the modified graphite reaches a mechanical melting state, thereby bonding the inorganic nanomaterials to the outer surface of the modified graphite, i.e., the sulfonated graphene / carbon nanotube coating.
[0040] According to an embodiment of the present invention, in step (5), the mass ratio of the inorganic nano material to the modified graphite is (0.1-0.5):100, for example, 0.1:100, 0.2:100, 0.3:100, 0.4:100 or 0.5:100. Studies have shown that when the mass ratio of the inorganic nano material to the modified graphite is less than 0.1:100, the content of the inorganic nano material on the surface of the carbonized graphite is too low to effectively improve the hardness of the graphite; when the mass ratio of the inorganic nano material to the modified graphite is greater than 0.5:100, the content of the inorganic nano material on the surface of the carbonized graphite is too high, which greatly reduces the capacity of the graphite and the hardness is too high.
[0041] According to an embodiment of the present invention, in step (6), the carbonization treatment is carried out under an inert atmosphere, and the inert atmosphere is nitrogen or argon.
[0042] According to an embodiment of the present invention, in step (6), the temperature of the carbonization treatment is 800-1200° C., for example, 800° C., 850° C., 900° C., 950° C., 1000° C., 1050° C., 1100° C., 1150° C. or 1200° C. The time of the carbonization treatment is 1-6 h, preferably 2-4 h, for example, 2 h, 3 h, 4 h, 5 h or 6 h.
[0043] The present invention also provides a modified graphite negative electrode material prepared by the method.
[0044] According to an embodiment of the present invention, the modified graphite negative electrode material has a core-shell structure; the core-shell structure includes a core, an inner shell and an outer shell; the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core includes graphite, the inner shell includes sulfonated graphene / carbon nanotubes, and the outer shell includes inorganic nanomaterials and amorphous carbon.
[0045] According to an embodiment of the present invention, the inorganic nanomaterial is embedded in the amorphous carbon in the form of discontinuous dots.
[0046] According to an embodiment of the present invention, the mass proportion of graphite in the modified graphite negative electrode material is 97-98.5wt%, for example, 97wt%, 97.5wt%, 98wt% or 98.5wt%.
[0047] The present invention also provides the use of the modified graphite negative electrode material, which is used for the negative electrode.
[0048] According to an embodiment of the present invention, a negative electrode is used for a lithium ion battery.
[0049] According to an embodiment of the present invention, the thickness of the negative electrode active material layer in the negative electrode is 205-350 μm, for example, 210 μm, 220 μm, 230 μm, 250 μm, 260 μm, 280 μm, 300 μm, 320 μm, 340 μm or 350 μm.
[0050] The present invention also provides a negative electrode, which includes a negative electrode current collector, a first negative electrode active material layer and a second negative electrode active material layer, wherein the first negative electrode active material layer is arranged on at least one side surface of the negative electrode current collector, and the second negative electrode active material layer is arranged on the surface of the first negative electrode active material layer; the second negative electrode active material layer includes the above-mentioned modified graphite negative electrode material.
[0051] According to an embodiment of the present invention, the first negative active material layer includes graphite.
[0052] According to an embodiment of the present invention, the graphite is at least one of artificial graphite and natural graphite.
[0053] According to an embodiment of the present invention, the median particle size of the graphite is 5-25 μm.
[0054] According to an embodiment of the present invention, the first negative electrode active material layer further includes a conductive agent and a binder.
[0055] According to an embodiment of the present invention, in the first negative electrode active material layer, the mass ratio of graphite, conductive agent and binder is (93-95):(3-5):2, for example, 93:5:2, 94:4:2 or 95:3:2.
[0056] According to an embodiment of the present invention, the second negative active material layer further includes a conductive agent and a binder.
[0057] According to an embodiment of the present invention, in the second negative electrode active material layer, the mass ratio of the modified graphite negative electrode material, the conductive agent and the binder is (93-95):(3-5):2, for example, 93:5:2, 94:4:2 or 95:3:2.
[0058] According to an embodiment of the present invention, the conductive agent is selected from any one or more of acetylene black, graphene and carbon nanotubes.
[0059] According to an embodiment of the present invention, the binder is selected from any one or more of SBR emulsion, sodium carboxymethyl cellulose, polyacrylonitrile and polyacrylic acid.
[0060] According to an embodiment of the present invention, the thickness of the first negative electrode active material layer is 180-300 μm, for example, 180 μm, 220 μm, 260 μm or 300 μm.
[0061] According to an embodiment of the present invention, the thickness of the second negative electrode active material layer is 25-50 μm, for example, 25 μm, 30 μm, 40 μm or 50 μm.
[0062] According to an embodiment of the present invention, the negative electrode has high rate performance, high energy density, and high first coulombic efficiency.
[0063] The present invention provides a method for preparing the above-mentioned negative electrode, the preparation method comprising:
[0064] (1) mixing graphite, a conductive agent, a binder and water uniformly to obtain an active slurry 1;
[0065] (2) uniformly mixing the modified graphite negative electrode material, the conductive agent, the binder and water to obtain an active slurry 2;
[0066] (3) The active slurry 1 is coated on at least one side of the negative electrode current collector, and then the active slurry 2 is coated on the surface of the active slurry 1, dried, rolled, and baked to obtain the negative electrode.
[0067] The present invention also provides a lithium ion battery, which comprises the above-mentioned negative electrode.
[0068] Beneficial effects of the present invention:
[0069] The present invention first disperses sulfonated graphene and amination carbon nanotubes in water, utilizes the electrostatic action of the sulfonic acid group on the surface of the sulfonated graphene and the amino group in the amination carbon nanotube to self-assemble and combine, obtains a three-dimensional network composite with high elasticity and high rigidity characteristics-sulfonated graphene / carbon nanotube, then coats the three-dimensional network composite on the graphite surface to obtain sulfonated graphene / carbon nanotube-coated graphite, then kneads the sulfonated graphene / carbon nanotube-coated graphite with asphalt, and fuses the inorganic nanomaterial in sequence, and then performs carbonization treatment, thereby forming a modified graphite negative electrode material with sulfonated graphene / carbon nanotube as an inner shell, amorphous carbon and inorganic nanomaterial as an outer shell, and graphite as a core. The inner shell has high elasticity and high rigidity, and the outer shell has high hardness. Due to the high hardness of the modified graphite negative electrode material, it will not deform during rolling, and it can ensure that the gaps of the stacked modified graphite negative electrode material particles in the negative electrode active material layer will not deform, thereby obtaining a negative electrode with a high gap ratio and low tortuosity. At the same time, the inorganic nanomaterials in the shell can also increase the roughness of the surface of the modified graphite negative electrode material, and further increase the gaps between the stacked modified graphite negative electrode material particles in the negative electrode active material layer, so as to be more conducive to obtaining a negative electrode with high porosity and low tortuosity. After the negative electrode is applied to a lithium-ion battery, when Li+ passes through these gaps in the negative electrode active material layer, it can quickly diffuse into the negative electrode, thereby having both high energy density and high rate performance; by controlling the content of the inorganic nanomaterials in the shell, the hardness of the shell can be kept within a reasonable range, avoiding the large hardness difference between the shell and the graphite core, resulting in the damage and shedding of the shell coating; at the same time, the introduction of the inner shell can also well improve the problem of the large hardness difference between the shell and the graphite core, further avoiding the damage and shedding of the shell coating, thereby obtaining a modified graphite negative electrode material with both high energy density and high first coulomb efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 This is a scanning electron microscope image of the modified graphite negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0071] The preparation method of the present invention will be described in further detail below in conjunction with specific examples. It should be understood that the following examples are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0072] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0073] The fusion machine used in the following embodiments is preferably the LHS fusion machine produced by Shandong Weifang Zhengyuan Powder.
[0074] The natural graphite used in the following examples is in the shape of a potato. 50 11μm, tap density 1.0g / cm 3 , with a specific surface area of 8.0m 2 / g, fixed carbon content 99.6wt%.
[0075] The D of the artificial graphite used in the following examples is 50 It is 11μm.
[0076] The asphalt used in the following examples is petroleum asphalt, with a softening point of 160°C and a particle size of 2.5 μm.
[0077] Example 1
[0078] (1) 0.5 g of sulfonated graphene was mixed with 1 liter of water, and ultrasonically dispersed for 5 hours, then 0.12 g of amino carbon nanotubes was added, and ultrasonic dispersion was continued for 4 hours to obtain a sulfonated graphene / carbon nanotube dispersion solution;
[0079] (2) transferring the sulfonated graphene / carbon nanotube dispersion solution of step (1) to a constant temperature water bath at 85° C., adding 100 g of natural graphite under stirring, and continuing stirring for 5 hours to obtain a suspension;
[0080] (3) filtering the suspension obtained in step (2), washing with pure water, and drying to obtain natural graphite coated with sulfonated graphene / carbon nanotubes;
[0081] (4) placing 100 g of the sulfonated graphene / carbon nanotube-coated natural graphite prepared in step (3) and 3 g of asphalt in a VC mixer, and treating at 100° C. at a rotation speed of 350 r / min for 120 min to obtain modified graphite;
[0082] (5) adding 100 g of the modified graphite obtained in step (4) and 0.3 g of Li3N (particle size of 15 nm) into a fusion machine for fusion to obtain a fusion product;
[0083] (6) The fusion product of step (5) is subjected to high-temperature carbonization in nitrogen at 800°C for 4 hours, and cooled to room temperature to obtain a modified graphite negative electrode material. The modified graphite negative electrode material has a core-shell structure, and the core-shell structure includes a core, an inner shell and an outer shell; the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core is natural graphite, the inner shell includes sulfonated graphene / carbon nanotubes, and the outer shell includes inorganic nanomaterials and amorphous carbon; wherein the inorganic nanomaterials are embedded in the amorphous carbon in a discontinuous dot shape. The modified graphite negative electrode material contains 97.99wt% natural graphite, 0.49wt% sulfonated graphene, 1.18wt% amorphous carbon, 0.29wt% inorganic nanomaterials, and the rest is carbon nanotubes.
[0084] (7) Natural graphite is mixed with acetylene black and sodium carboxymethyl cellulose in a mass ratio of 94:4:2, and water is added at a ratio of 54% of the system solid content and the mixture is fully stirred to prepare an active slurry 1; the modified graphite negative electrode material of step (6) is mixed with acetylene black and sodium carboxymethyl cellulose in a mass ratio of 94:4:2, and water is added at a ratio of 54% of the system solid content and the mixture is fully stirred to prepare an active slurry 2.
[0085] (8) Active slurry 1 is coated on the negative electrode current collector Cu foil, and then active slurry 2 is coated on the surface of active slurry 1, and the negative electrode is obtained after drying, rolling and baking. The negative electrode comprises a negative electrode current collector, a first negative electrode active material layer and a second negative electrode active material layer, wherein the first negative electrode active material layer is arranged on both sides of the negative electrode current collector, and the second negative electrode active material layer is arranged on the surface of the first negative electrode active material layer; the first negative electrode active material layer comprises natural graphite, and the thickness of the first negative electrode active material layer is 220 μm; the second negative electrode active material layer comprises a modified graphite negative electrode material, and the thickness of the second negative electrode active material layer is 30 μm.
[0086] Example 2
[0087] (1) 0.8 g of sulfonated graphene was mixed with 1 liter of water, and ultrasonically dispersed for 5 hours, then 0.2 g of amino-modified carbon nanotubes was added, and ultrasonic dispersion was continued for 4 hours to obtain a sulfonated graphene / carbon nanotube dispersion solution;
[0088] (2) transferring the sulfonated graphene / carbon nanotube dispersion solution of step (1) to a constant temperature water bath at 85° C., adding 100 g of natural graphite under stirring, and continuing stirring for 5 hours to obtain a suspension;
[0089] (3) filtering the suspension obtained in step (2), washing with pure water, and drying to obtain natural graphite coated with sulfonated graphene / carbon nanotubes;
[0090] (4) placing 100 g of the sulfonated graphene / carbon nanotube-coated natural graphite prepared in step (3) and 5 g of asphalt in a VC mixer, and treating at 100° C. at a rotation speed of 350 r / min for 120 min to obtain modified graphite;
[0091] (5) adding 100 g of the modified graphite obtained in step (4) and 0.5 g of TiO2 (particle size of 10 nm) into a fusion machine for fusion to obtain a fusion product;
[0092] (6) The fusion product of step (5) is subjected to high-temperature carbonization in nitrogen at 850°C for 4 hours, and cooled to room temperature to obtain a modified graphite negative electrode material. The modified graphite negative electrode material has a core-shell structure, and the core-shell structure includes a core, an inner shell and an outer shell; the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core is natural graphite, the inner shell includes sulfonated graphene / carbon nanotubes, and the outer shell includes inorganic nanomaterials and amorphous carbon; wherein the inorganic nanomaterials are embedded in the amorphous carbon in a discontinuous dot shape. The modified graphite negative electrode material has a natural graphite content of 96.52wt%, a sulfonated graphene content of 0.77wt%, an amorphous carbon content of 1.93wt%, an inorganic nanomaterial content of 0.58wt%, and the rest is carbon nanotubes.
[0093] (7) Natural graphite is mixed with acetylene black and sodium carboxymethyl cellulose in a mass ratio of 94:4:2, and water is added at a ratio of 54% of the system solid content and the mixture is fully stirred to prepare an active slurry 1; the modified graphite negative electrode material of step (6) is mixed with acetylene black and sodium carboxymethyl cellulose in a mass ratio of 94:4:2, and water is added at a ratio of 54% of the system solid content and the mixture is fully stirred to prepare an active slurry 2.
[0094] (8) Apply active slurry 1 to the negative electrode current collector Cu foil, then apply active slurry 2 to the surface of active slurry 1, dry, roll and bake to obtain a negative electrode. The negative electrode comprises a negative electrode current collector, a first negative electrode active material layer and a second negative electrode active material layer, wherein the first negative electrode active material layer is arranged on both sides of the negative electrode current collector, and the second negative electrode active material layer is arranged on the surface of the first negative electrode active material layer; the first negative electrode active material layer comprises natural graphite, and the thickness of the first negative electrode active material layer is 220 μm; the second negative electrode active material layer comprises a modified graphite negative electrode material, and the thickness of the second negative electrode active material layer is 30 μm.
[0095] Example 3
[0096] (1) 0.6 g of sulfonated graphene was mixed with 1 liter of water, and ultrasonically dispersed for 5 hours, then 0.07 g of amino carbon nanotubes was added, and ultrasonic dispersion was continued for 4 hours to obtain a sulfonated graphene / carbon nanotube dispersion solution;
[0097] (2) transferring the sulfonated graphene / carbon nanotube dispersion solution of step (1) to a constant temperature water bath at 85° C., adding 100 g of artificial graphite under stirring, and continuing stirring for 5 hours to obtain a suspension;
[0098] (3) filtering the suspension obtained in step (2), washing with pure water, and drying to obtain artificial graphite coated with sulfonated graphene / carbon nanotubes;
[0099] (4) placing 100 g of the sulfonated graphene / carbon nanotube-coated artificial graphite prepared in step (3) and 3 g of asphalt in a VC mixer, and treating at 100° C. at a rotation speed of 450 r / min for 100 min to obtain modified graphite;
[0100] (5) adding 100 g of the modified graphite obtained in step (4) and 0.2 g of Al2O3 (particle size of 15 nm) into a fusion machine for fusion to obtain a fusion product;
[0101] (6) The fusion product of step (5) is subjected to high-temperature carbonization in nitrogen at 900°C for 4 hours, and cooled to room temperature to obtain a modified graphite negative electrode material. The modified graphite negative electrode material has a core-shell structure, and the core-shell structure includes a core, an inner shell and an outer shell; the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core is artificial graphite, the inner shell includes sulfonated graphene / carbon nanotubes, and the outer shell includes inorganic nanomaterials and amorphous carbon; wherein the inorganic nanomaterials are embedded in the amorphous carbon in a discontinuous dot shape. The artificial graphite content of the modified graphite negative electrode material is 97.97wt%, the sulfonated graphene content is 0.58wt%, the amorphous carbon content is 1.18wt%, the inorganic nanomaterial content is 0.2wt%, and the rest is carbon nanotubes.
[0102] (7) After artificial graphite is mixed with acetylene black and sodium carboxymethyl cellulose in a mass ratio of 94:4:2, water is added at a ratio of 54% of the system solid content and the mixture is fully stirred to prepare active slurry 1; after the modified graphite negative electrode material of step (6) is mixed with acetylene black and sodium carboxymethyl cellulose in a mass ratio of 94:4:2, water is added at a ratio of 54% of the system solid content and the mixture is fully stirred to prepare active slurry 2.
[0103] (8) Active slurry 1 is coated on the negative electrode current collector Cu foil, and then active slurry 2 is coated on the surface of active slurry 1, and the negative electrode is obtained after drying, rolling and baking. The negative electrode comprises a negative electrode current collector, a first negative electrode active material layer and a second negative electrode active material layer, wherein the first negative electrode active material layer is arranged on both sides of the negative electrode current collector, and the second negative electrode active material layer is arranged on the surface of the first negative electrode active material layer; the first negative electrode active material layer comprises artificial graphite, and the thickness of the first negative electrode active material layer is 240 μm; the second negative electrode active material layer comprises a modified graphite negative electrode material, and the thickness of the second negative electrode active material layer is 40 μm.
[0104] Example 4
[0105] (1) 0.7 g of sulfonated graphene was mixed with 1 liter of water, and ultrasonically dispersed for 5 hours, then 0.1 g of amino-modified carbon nanotubes was added, and ultrasonic dispersion was continued for 4 hours to obtain a sulfonated graphene / carbon nanotube dispersion solution;
[0106] (2) transferring the sulfonated graphene / carbon nanotube dispersion solution of step (1) to a constant temperature water bath at 85° C., adding 100 g of artificial graphite under stirring, and continuing stirring for 5 hours to obtain a suspension;
[0107] (3) filtering the suspension obtained in step (2), washing with pure water, and drying to obtain artificial graphite coated with sulfonated graphene / carbon nanotubes;
[0108] (4) placing 100 g of the sulfonated graphene / carbon nanotube-coated artificial graphite prepared in step (3) and 4 g of asphalt in a VC mixer, and treating at 100° C. at a rotation speed of 200 r / min for 120 min to obtain modified graphite;
[0109] (5) adding 100 g of the modified graphite obtained in step (4) and 0.4 g of VN (particle size of 15 nm) into a fusion machine for fusion to obtain a fusion product;
[0110] (6) The fusion product of step (5) is subjected to high-temperature carbonization in nitrogen at 950°C for 2h, and cooled to room temperature to obtain a modified graphite negative electrode material. The modified graphite negative electrode material has a core-shell structure, and the core-shell structure includes a core, an inner shell and an outer shell; the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core is artificial graphite, the inner shell includes sulfonated graphene / carbon nanotubes, and the outer shell includes inorganic nanomaterials and amorphous carbon; wherein the inorganic nanomaterials are embedded in the amorphous carbon in a discontinuous dot shape. The artificial graphite content of the modified graphite negative electrode material is 97.28wt%, the sulfonated graphene content is 0.68wt%, the amorphous carbon content is 1.56wt%, the inorganic nanomaterial content is 0.39wt%, and the rest is carbon nanotubes.
[0111] (7) After artificial graphite is mixed with acetylene black and sodium carboxymethyl cellulose in a mass ratio of 94:4:2, water is added at a ratio of 54% of the system solid content and the mixture is fully stirred to prepare active slurry 1; after the modified graphite negative electrode material of step (6) is mixed with acetylene black and sodium carboxymethyl cellulose in a mass ratio of 94:4:2, water is added at a ratio of 54% of the system solid content and the mixture is fully stirred to prepare active slurry 2.
[0112] (8) Active slurry 1 is coated on the negative electrode current collector Cu foil, and then active slurry 2 is coated on the surface of active slurry 1, and the negative electrode is obtained after drying, rolling and baking. The negative electrode comprises a negative electrode current collector, a first negative electrode active material layer and a second negative electrode active material layer, wherein the first negative electrode active material layer is arranged on both sides of the negative electrode current collector, and the second negative electrode active material layer is arranged on the surface of the first negative electrode active material layer; the first negative electrode active material layer comprises artificial graphite, and the thickness of the first negative electrode active material layer is 240 μm; the second negative electrode active material layer comprises a modified graphite negative electrode material, and the thickness of the second negative electrode active material layer is 40 μm.
[0113] Comparative Example 1
[0114] (1) Natural graphite, acetylene black and sodium carboxymethyl cellulose were mixed in a mass ratio of 94:4:2, and water was added so that the solid content of the system was 54%, and the mixture was fully stirred to prepare an active slurry 1.
[0115] (2) The active slurry 1 is coated on the negative electrode current collector Cu foil, and then dried, rolled and baked to obtain a negative electrode. The negative electrode comprises a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer is arranged on both sides of the negative electrode current collector; the negative electrode active material layer comprises natural graphite, and the thickness of the negative electrode active material layer is 250 μm.
[0116] Comparative Example 2
[0117] (1) Artificial graphite, acetylene black and sodium carboxymethyl cellulose were mixed in a mass ratio of 94:4:2, and water was added so that the solid content of the system was 54%, and the mixture was fully stirred to prepare an active slurry 1.
[0118] (2) The active slurry 1 is coated on the negative electrode current collector Cu foil, and then dried, rolled and baked to obtain a negative electrode. The negative electrode comprises a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer is arranged on both sides of the negative electrode current collector; the negative electrode active material layer comprises natural graphite, and the thickness of the negative electrode active material layer is 280 μm.
[0119] Full battery testing method: The negative electrode sheet prepared in the embodiment and the comparative example is used as the negative electrode, and the lithium cobalt oxide positive electrode sheet and 1M-LiPF6+EC:DEC:DMC (volume ratio 1:1:1) solution are used as the electrolyte to assemble a full battery. Assembly of the lithium ion battery: The lithium cobalt oxide positive electrode sheet, the negative electrode sheet prepared in the above embodiment or the comparative example and the diaphragm are assembled in the order of diaphragm / negative electrode / diaphragm / positive electrode / diaphragm to obtain a battery cell; the bare battery cell is encapsulated in a shell, baked to remove water, and then the electrolyte is injected. After the processes of formation, exhaust, and capacity separation, a lithium ion battery is obtained.
[0120] The prepared lithium-ion battery was subjected to performance tests:
[0121] The test temperature is 23±2℃, and the battery is charged at a constant current of 0.1C to 4.2±0.01V, and then charged at a constant voltage with a cutoff current of 0.05C; let it sit for 10 minutes, and then discharged at 0.1C with a cutoff voltage of 3.0V, and the capacity is recorded as the initial capacity in the rate test; then charged at a constant current of 0.1C to 4.2±0.01V, and then charged at a constant voltage with a cutoff current of 0.05C; let it sit for 10 minutes; then the lithium-ion battery prepared from natural graphite is discharged at 0.1C, 0.2C, 0.4C, 0.8C, and 1C, respectively, with a cutoff voltage of 3.0V, and the capacity is recorded as the rate capacity of 0.1C, 0.2C, 0.4C, 0.8C, and 1C. The lithium-ion batteries prepared with artificial graphite were discharged at 1C, 1.5C, 3C, 5C and 8C, respectively, with a cut-off voltage of 3.0V. The capacity was recorded and used as the rate capacity of 1C, 1.5C, 3C, 5C and 8C.
[0122] Table 1 Performance test results of lithium-ion batteries (natural graphite)
[0123]
[0124] Table 2 Performance test results of lithium-ion battery (artificial graphite)
[0125]
[0126] It can be seen from the above performance test results that the modified graphite negative electrode material prepared by the present invention has excellent rate performance under thick electrodes, while also taking into account high initial coulombic efficiency and high energy density. Comparative Examples 1 and 2 are thick pole pieces made of natural graphite and artificial graphite, respectively. Due to the soft texture and low hardness of graphite particles, they will deform when subjected to vertical pressure during the rolling stage, which makes the gaps between the stacked graphite particles on the surface of the negative electrode sheet significantly smaller, resulting in a significant deterioration in the rate of Li+ in the thick electrode due to the extension of the charge transfer path.
[0127] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a modified graphite negative electrode material, the preparation method comprising the following steps: (1) mixing sulfonated graphene with water, performing ultrasonic dispersion, then adding aminated carbon nanotubes, and continuing ultrasonic dispersion to obtain a sulfonated graphene / carbon nanotube dispersion solution; (2) transferring the sulfonated graphene / carbon nanotube dispersion solution of step (1) into a constant temperature water bath, adding graphite, and obtaining a suspension; (3) filtering, washing and drying the suspension obtained in step (2) to obtain sulfonated graphene / carbon nanotube-coated graphite; (4) adding the sulfonated graphene / carbon nanotube-coated graphite of step (3) and asphalt into a mixer and kneading them to obtain modified graphite; (5) adding the modified graphite and inorganic nanomaterials of step (4) into a fusion machine for fusion to obtain a fusion product; (6) Carbonizing the fusion product of step (5) to obtain the modified graphite negative electrode material.
2. The preparation method according to claim 1, wherein In step (1), the mass of sulfonated graphene added to each milliliter of water is (0.5-1.0) mg. Preferably, in step (1), the mass ratio of the amino-modified carbon nanotubes to the sulfonated graphene is (10-30):
100. Preferably, in step (2), the median particle size of the graphite is 5-25 μm. Preferably, in step (2), the mass ratio of the sulfonated graphene to graphite is (0.5-1):
100.
3. The preparation method according to claim 1 or 2, wherein In step (4), the asphalt is selected from coal asphalt or petroleum asphalt. Preferably, in step (4), the asphalt is in powder form with a particle size of 1-3 μm. Preferably, in step (4), the mass ratio of the asphalt to the sulfonated graphene / carbon nanotube-coated graphite is (1-5):
100. Preferably, in step (5), the inorganic nanomaterial is selected from at least one of VN, Li3N, CoN, NiN, AlN, TiO2 and Al2O3. Preferably, in step (5), the particle size of the inorganic nanomaterial is 10-30 nm. Preferably, in step (5), the mass ratio of the inorganic nanomaterial to the modified graphite is (0.1-0.5):
100. Preferably, in step (6), the temperature of the carbonization treatment is 800-1200° C., and the time of the carbonization treatment is 1-6 hours.
4. A modified graphite negative electrode material prepared by the method according to any one of claims 1 to 3.
5. The modified graphite negative electrode material according to claim 4, wherein The modified graphite negative electrode material has a core-shell structure; the core-shell structure comprises a core, an inner shell and an outer shell; the inner shell is coated on the surface of the core, and the outer shell is coated on the surface of the inner shell; the core comprises graphite, the inner shell comprises sulfonated graphene / carbon nanotubes, and the outer shell comprises inorganic nanomaterials and amorphous carbon. Preferably, the inorganic nanomaterial is embedded in the amorphous carbon in the form of discontinuous dots. Preferably, the mass percentage of graphite in the modified graphite negative electrode material is 96-98.5wt%.
6. Use of the modified graphite negative electrode material according to claim 4 or 5, which is used for a negative electrode.
7. The use according to claim 6, wherein The thickness of the negative electrode active material layer in the negative electrode is 205-350 μm.
8. A negative electrode, comprising a negative electrode current collector, a first negative electrode active material layer and a second negative electrode active material layer, wherein the first negative electrode active material layer is arranged on at least one side surface of the negative electrode current collector, and the second negative electrode active material layer is arranged on the surface of the first negative electrode active material layer; the second negative electrode active material layer comprises the modified graphite negative electrode material according to claim 4 or 5.
9. The negative electrode according to claim 8, wherein The first negative electrode active material layer includes graphite. Preferably, the thickness of the first negative electrode active material layer is 180-300 μm; the thickness of the second negative electrode active material layer is 25-50 μm. 10 . A lithium ion battery, comprising the negative electrode according to claim 8 or 9.
Citation Information
Cited By
Three-dimensional modified graphite composite material and lithium ion battery
CN120727822A
Modified graphite negative electrode material, and preparation method therefor and use thereof
WO2026077093A1